Using a 4K three-dimensional exoscope system (Vitom 3D) for mastoid surgery during the coronavirus disease 2019 pandemic - Ally, M (J Laryngol Otol, 2021)
OBJECTIVE: Microscopic surgery is currently considered the ‘gold standard’ for middle-ear, mastoid and lateral skull base surgery. The coronavirus disease 2019 pandemic has made microscopic surgery more challenging to perform. This work aimed to demonstrate the feasibility of the Vitom 3D system, which integrates a high-definition (4K) view and three-dimensional technology for ear surgery, within the context of the pandemic. METHOD: Combined approach tympanoplasty and ossiculoplasty were performed for cholesteatoma using the Vitom 3D system exclusively. RESULTS: Surgery was performed successfully. The patient made a good recovery, with no evidence of residual disease at follow up. The compact system has excellent depth of field, magnification and colour. It enables ergonomic work, improved work flow, and is ideal for teaching and training. CONCLUSION: The Vitom 3D system is considered a revolutionary alternative to microscope-assisted surgery, particularly in light of coronavirus disease 2019. It allows delivery of safe otological surgery, which may aid in continuing elective surgery.